How prime ministers decide - Chowdhury, Neerja (New Delhi : Aleph Book Company, 2023)
"India$1 (Bs prime ministers have taken decisions that changed the course of the country$1 (Bs history. This book by Neerja Chowdhury, an award-winning journalist and political commentator, goes beyond the news headlines to provide an eye-opening account of how some of the most important political decisions in independent India were taken. The author analyses the operating styles of the country$1 (Bs prime ministers through the prism of six decisions of historic significance. These are as follows: the strategy that Indira Gandhi devised to return to power in 1980, after her humiliating defeat post the Emergency in 1977; the errors of judgment that led Rajiv Gandhi to undo the Supreme Court$1 (Bs judgment in the Shah Bano case; V. P. Singh$1 (Bs implementation of the Mandal Commission Report to save his government which forever changed the face of contemporary politics; P. V. Narasimha Rao$1 (Bs masterful indecision that resulted in the demolition of the Babri Masjid; the rapidly changing political scenarios that turned the avowed pacifist Atal Bihari Vajpayee into a nuclear hawk who greenlighted the testing of nuclear devices; and the mild and professorial Manmohan Singh, widely regarded as one of the country$1 (Bs weakest prime ministers, who defied interest groups and foes within the political establishment to seal a historic nuclear deal with the United States$1 (Band upgraded the bilateral relationship to a new level. Based on hundreds of interviews that the author conducted with prime ministers, key figures in the political establishment, bureaucrats, aides, policymakers, and even fixers$1 (Bthe book provides remarkable insights that have been gleaned over forty years of high-level reporting on the national political scene. How Prime Ministers Decide is an unparalleled book about modern Indian politics which will change the way we view how prime ministers govern the country."--s
Keywords: India -- Prime ministers